Prawicowe i lewicowe partie populistyczne po wyborach do Parlamentu Europejskiego w 2014 roku na przykładzie Wolnościowej Partii Austrii oraz Partii Lewicy w Niemczech - Miecznikowska, Justyna (Rocznik Integracji Europejskiej, 2015)
The research objective of this paper is to analyse European programmes of the right wing, populist Freedom Party of Austria (FPÖ) and the left wing, populist German Left Party (Die Linke), to present their 2014 election campaigns for the European Parliament, and also to assess the activities undertaken by Members of the European Parliament of these political groups on the forum of the eighth EP. The reflections presented in this work were divided into four parts. First, the analysis of a large body of literature referring to populism is made and selected concepts for indicating the characteristic features of populist groups are proposed. Next, the European programmes of the Freedom Party of Austria and the German Left party are analysed. Then, the main subjects around which the political campaign to the EP of right- and left-wing populists was concentrated are indicated. In the third part, the analysis covers the EP election results and the voter support gained by the respective groups in relation to previous European elections in which both populist groups participated. Finally, the fourth part of the paper lists the areas of ac- tivities and the tools for parliamentary work used by the MEPs from FPÖ and the Left Party, including an assessment of their influence on the policy of the current EP.